The prospect of antimicrobial peptides from Bacillus species with biological control potential against insect pests and diseases of economic importance in agriculture, forestry and fruit tree production - Henry B. Ajuna; Hyo-In Lim; Jae-Hyun Moon; Sang-Jae Won; Vantha Choub; Su-In Choi; Ju-Yeol Yun; Young Sang Ahn (Biotechnology & Biotechnological Equipment)
Plant diseases and insect pests cause tremendous losses in agriculture, forestry and fruit tree production worldwide. The continuous application of chemical pesticides in the control of pests and diseases is increasingly becoming undesirable due to the associated health risks, environmental pollution and pesticide resistance. Biological control strategies are generally safer and more sustainable alternatives in plant disease and insect pest management. Bacillus species have been widely studied and commercialized as biocontrol agents, due to their ability to produce a wide range of versatile antimicrobial lipopeptides, polyketides, insecticidal toxins and the elicitation for induced systemic resistance (ISR). This review focuses on the biocontrol prospects of antimicrobial peptides from Bacillus sp. and the elicitation of ISR against plant diseases and insect pests of economic importance in agriculture, forestry and fruit tree production. The review summarizes the biocontrol reports of antimicrobial and insecticidal peptides from Bacillus sp. including lipopeptides, polyketides, bacterial volatile compounds and the elicitation of ISR against various phytopathogens and insect pests and the mechanisms involved in their antimicrobial/insecticidal activity and plant defence responses. This study will help researchers identify the gaps for future research in the application of Bacillus sp. in the eco-friendly management of plant diseases and insect pests.